Pemanfaatan Formula Coating untuk Meningkatkan Mutu dan Kesehatan Benih Padi (Oryza Sativa L.) Selama Penyimpanan - Aloysius Rusae; Anna Tefa; Maria Matilde Nesi Seran (Savana Cendana, 2020)
Rice in one of the food commodities because it is widely consumed by most Indonesian people. The purpose of this study is to improve the quality and health of rice seeds throuhg a coating process. This research was conducted at the Faculty of agriculture at the University of Timor in February-May 2019. This study used a completely randomized factorial design. The first factor is to do a coating consisting of 3 levels, namely without coating, coating whit PGPR, coating with MOL. The second factor is the deposit period consisting of 4 levels, namely: no storage, ist month storage, 2nd month storage, and 3rd month storage. The results showed that there was an interaction in all the observed parameters except for the observed parameters of normal germination weight, with the best treatment combination being the coating treatment with PGPR with a storage time of 1 month as indicated by the observed parameters of the best germination, best vigor index, and lowest incidence of disease. normal, with the best treatment combination is a coating treatment with PGPR with a storage time of 1 month as indicated by the observation parameters of the best germination, the best vigor index, and the lowest incidence of disease.